Determine the Adverse Outcomes of Direct Antiviral Therapy in Patients with Hepatitis C Infection - Mahesh Kumar Wadhwa, Daud Ghilzai, Ali Hyder Mugheri, Sania, Kamran Ali Memon, Javeriya Mariam, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the outcome of direct antiviral therapy in patients with hepatitis C infection. Study Design: Prospective study Place and Duration of Study: Department of Gastroenterology, Chandka Medical College, Larkana from 1st July 2021 to 30th June 2022. Methodology: Two hundred hepatitis C patients after obtaining their informed consent were enrolled. Each patient was analyzed for phenotype and genotype of hepatitis C infection through polymerase chain reaction (PCR). The stage of cirrhosis was confirmed through the available of definition of liver biopsy interpretation. Non-invasive tests were also conducted for confirming the fibrotic stage. These tests included APRI, FIB-4 as well as transient-elastography. The patients selected for participation were between age group of 35-65years after taking informed written consent. The sustained viral response assessment was conducted through determining a 12-week viral load after the initiation of treatment of direct acting antivirals as per the available protocols through hepatic association. Results: The mean age of the patients were 57±9.5 years with majority being males such as 60%. The majority of the cases were having genotype 3 followed by genotype 1. Within the total cases the adverse outcomes were noticed in 5% of the cases Conclusion: These drug regimens show effectiveness in low income countries and proved to be safe Sofosbuvir-based drug choice for hepatitis C treatment. Keywords: Genotyping, Antiviral drugs, Regimens, Prevalence, Efficacy